2018
DOI: 10.18820/24150525/comm.v23.2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between traditional and digital media as an influence on generational consumer preference

Abstract: Marketers, advertisers and media planners often turn to reliable data on target markets to make decisions regarding the selection and use of media, allowing practitioners to communicate the message optimally and cost-effectively to the target audience. Decisions in media planning and media selection are only possible if information on media use patterns is up-to-date. Hence, understanding media consumers allows marketers to tailor specifically to a target market. This article presents an initial inquiry into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In line with the results of [33], male respondents had a more negative opinion of programmatic advertising (see also [34,36]). The groups who valued programmatic advertising most negatively were the unemployed and retired, which contradicts the results of several other studies that reported that these negative feelings were given by respondents who were employed in companies [35,37]. The participants over 45 years old used ad-blockers most frequently, as did the youngest age group between 14 and 24 years old.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In line with the results of [33], male respondents had a more negative opinion of programmatic advertising (see also [34,36]). The groups who valued programmatic advertising most negatively were the unemployed and retired, which contradicts the results of several other studies that reported that these negative feelings were given by respondents who were employed in companies [35,37]. The participants over 45 years old used ad-blockers most frequently, as did the youngest age group between 14 and 24 years old.…”
Section: Discussioncontrasting
confidence: 83%
“…Another study concluded that adults were more interested in digital signage, a form of advertising, than young people [34]. Young people were reported to use ad-blockers less than older people [28,35]. The following hypotheses were formulated using this information: Hypothesis 1 (H1).…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…Consumer preference is also closely related to the propaganda by the media. According to Nhedzi's study on consumer preference between traditional and digital media, the data shows that more and more people have become more open-minded toward new service forms [2]. This study also suggested that the reformation of traditional media lets people spend more time on these digital platforms, which also means that digital media's content has become increasingly important in people's minds.…”
Section: Mediamentioning
confidence: 91%